Some problems of intergovernmental relations of the Republic of Kazakhstan in the context of globalization - Zenchenko, S.V.; Kurmanalina, А.К. (BUKETOV BUSINESS REVIEW, 2017)
The article presents the judgment of the authors to improve the structure of the state budget of Kazakhstan on issues of a more clear division of responsibilities between all levels of government, are considered controversial moments on regulating inter-budgetary relations between Republican budget and the budgets of the regions, revealed the status of intergovernmental relations by the example of the dynamics of transfers and budget loans represented the amount of subventions allocated to the regions for 2013-2015. Special attention is focused on the need to develop a methodological approach to the study of these problems, taking into account the diversity of local conditions that influence management decisions. Presents the author's vision on the need for comprehensive studies of the problems of interbudgetary relations of the Republic of Kazakhstan in conditions of globalization. The main goal of the research in this scientific article has been focused on improving the system of state planning. The methodology of scientific research based on the study of the scientific views of scientists on concepts such as the state budget, intergovernmental relations. The conclusions on the modernization of budgetary relations, improving the state planning system, review the role of local budgets as the chief conductor of the state policy in the region and identified the problem of intergovernmental relations in Kazakhstan, with the generalization of positive and negative trends in the regulatory mechanisms of inter-budgetary relations, expressed suggestions on ways to improve intergovernmental relations in the Republic of Kazakhstan mechanism.